2016
DOI: 10.1002/ijc.30407
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of cutaneous melanoma in Sweden—Stage‐specific survival and rate of recurrence

Abstract: Cutaneous malignant melanoma (CMM) incidence is increasing globally, making a thorough understanding of the disease and its outcomes essential for optimizing care even more urgent. In this population-based, retrospective study, we investigated stage-specific survival and recurrence/progression rates of CMM among patients diagnosed in Stockholm County Council during 2005-2012, before the wide introduction of targeted therapy. A total of 3,554 CMM patients from the Stockholm Melanoma Register were included. Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
52
2
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 35 publications
7
52
2
7
Order By: Relevance
“…This study has shown that recurrence data could be collected from other registries in a region in Sweden with good structured data. A previous Swedish study from the Stockholm/Gotland region studied stage‐specific risk of progression/recurrence . The proportion of patients with metastasis found in that study was somewhat higher compared to our findings, but the inclusion criteria differed as the study included clinical stages III‐IV patients and also patients with a positive SNB.…”
Section: Discussioncontrasting
confidence: 84%
“…This study has shown that recurrence data could be collected from other registries in a region in Sweden with good structured data. A previous Swedish study from the Stockholm/Gotland region studied stage‐specific risk of progression/recurrence . The proportion of patients with metastasis found in that study was somewhat higher compared to our findings, but the inclusion criteria differed as the study included clinical stages III‐IV patients and also patients with a positive SNB.…”
Section: Discussioncontrasting
confidence: 84%
“…In addition, the OS of patients in stage 4 showed disparities depending on the metastases sites, where brain metastasis had the worst prognosis and was approximately seven times higher than that for lung metastasis . Meanwhile, in one study conducted in Sweden, the 5‐year stage‐specific survival were as follows: 91.4% for stage 1, 61.8% for stage 2, 56.9% for stage 3 and 24.6% for stage 4 . Accordingly, in our study, patients in stage 4 had significantly lower survival rates compared with those in other stages.…”
Section: Discussionsupporting
confidence: 38%
“…This may be a modest underestimation of the true stage II incidence because SEER data do not contain staging data for approximately 9% of cases. European data sets suggest that a range from 10% to 20% of all new cases present as stage II, smaller fractions present with stage III or IV disease, and the majority of new cases present as stage I, similar to US data (Fig. ) …”
Section: Introductionsupporting
confidence: 78%
“…Data from the Surveillance, Epidemiology, and End Results (SEER) program database were estimated using the percentage frequency distribution by stage derived from SEER*Stat software; specifically, patients who had newly diagnosed with melanoma in years 2011 through 2015 were used, and stage group was derived from the American Joint Committee on Cancer, 7th edition, for all ages combined. Data sources include the National Cancer Institute, 2018; Rockberg et al, 2016; and Schoffer et al, 2016 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation